KESANGGUPAN BERPRODUKSI UMKM UNTUK KERAMIK BERFOTOKATALIS PRODUK PAJANGAN DINDING DAN PAJANGAN MEJA - Nyoman Normal; Wiryawan Suputra Gumi (Forum Manajemen STIMI Handayani Denpasar, 2022)
Photocatalyst ceramic is a product that has the potential to be developed by MSMEs when sales and income decline. Photocatalyst ceramics act as disposable, display, and functional objects. However, it is not yet known whether MSMEs are capable of producing wall displays or table displays. The purpose of this study: to determine the potential of MSMEs to produce wall display products and table displays, to examine the differences in the ability of MSMEs to produce wall display and table display products, and to disseminate photocatalyzed ceramic products as a result of BRIN's research which has the prospect of being developed by MSMEs. The research method used is: the interview method and the list of questions, the stratified purposive sampling, and the difference test of two independent samples. The results showed: 1) The biggest opportunity for MSMEs to produce photocatalytic ceramics for wall displays is Panji Ceramic, while table display products are Grazinia Ceramic; 2) There is no difference in the ability of MSMEs to produce photocatalyzed ceramics for wall displays and table displays; and 3) Photocatalyst ceramic products resulting from BRIN's research can be developed by ceramic MSMEs, including: (a) wall displays: meru motif tiles, songket motif tiles, and earthenware lamp holders; and (b) table displays: coral leaf ashtray, classic lampshade, modern lampshade, flower vase, pyramid-shaped lampshade, and ape-patterned earthenware flower pot.